แนวทางการลงทุนการจัดสิ่งแวดล้อมศึกษาเพื่อเสริมสร้างความสามารถในการจัดการขยะครัวเรือนขององค์การบริหารส่วนตำบลขนาดเล็ก - อารีรัตน์ ภาคพิธเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The objectives of this research are to: 1) study the state of investment and the environmental education provision model for the household solid waste management (HSWM) of small subdistrict administrative organizations (SSAO); 2) analyze the investment returns on the environmental education provision in HSWM of SSAO; and 3) propose the investment guidelines on environmental education provision to strengthen the ability of SSAO in HSWM. The research studies are conducted by Content Analysis; Analytic Induction, the state of investment and the environmental education provision model for the HSWM of SSAO; and Analysis of the investment returns on the environmental education provision model for the HSWM of SSAO. The 4 sites of case study are: 1) Kohthuad in Nakorn Sri Dharmarah province, 2) Thuemtong in Nan province, 3) Suanluang in Samut Songkhram province, and 4) Salakdai in Surin Province. From the findings, the investment guidelines for environmental education provision to strengthen the ability of SSAO in HSWM can be drafted and proposed to the group of experts for consideration. The research results found that: 1) SSAO implemented the human capital, resources capital and social capital to be the capital for minimizing restrictions by the investment model of environmental education provision in HSWM of SSAO which was divided into 2 models: (1.1) joint investment and joint expansion. (1.1.1) joint investment was the type of investment which the SSAO were co-thinking, personnel co-planning, co-supporting and co-inspecting; and (1.1.2) joint expansion. SSAO were the co-extending and co-networking with the local districts, government organizations and people in the community; (1.2) The environmental education provision model in HSWM was building up the conscious mind and awareness of local people including to increase the mechanic effectiveness of the solid waste management in their community. The goal was to develop human, a better environment and quality of life. The project’s target groups differentiated according to the community context and problems on sites. Environmental education activities were 5 aspects of development: ideas, process, improving, model and extending. Factors effected to the investment for environmental education provision in HSWM were divided into 5 aspects: (1) Policies which emphasized the human centered development; (2) Administers’ concepts which were able to integrate the environmental education provision model; (3) Role of SSAO which could minimize the restricted ability by connecting to the communities; (4) The Applied Community Potentialities or the joint investment for being the highest mutual benefit; and (5) Community preparation for understanding, having co- conscious mind and joining the activities. 2) The investment returns analysis on the environmental education provision in HSWM were worthwhile. The factors, effected to the worthwhile investment, were the conditions of solid waste, social capital, various joint investment, and joint expansion. 3) This research proposed the investment guidelines for environmental education provision in HSWM of SSAO as follow: (1) developed the human resources in community; (2) developed the community participating process; (3) organized the integrated activities in environmental education; (4) organized the environmental for managing the community environment; (5) got the community potentialities; (6) used various methods in the capital management; (7) connected activities between the subdistrict administrative organizations and communities; (8) had the inspection process and data retrieval from the investment; and (9) developed the environmental education provision model for increasing the investment results.